(untitled) (diségno, 2024)
This contribution reflects on the complexities and new challenges that representation faces in the context of landscape planning, after the innovations introduced since 2004 in the Piani paesaggistici with the Codice dei beni culturali e del paesaggio. Specifically, an analysis is proposed of the different types of representations present in the Piani paesaggistici: the more interpretative ones are linked to the act of knowing, which in the Piani paesaggistici culminates in the identification of Ambiti di paesaggio; the more technical representations, on the other hand, are related to the sphere of action, which in this contribution refers to the practice of landscape protection through the activities of surveying, mapping and digitizing landscape assets. The transition from analog representation of documents to the digital representation in the Piano paesaggistico, the significance of base cartography, and the interpretation of the landscape undertaken by the Regions, which is translated into the choice of graphic symbols used, are all themes of reflection that serve as a starting point to consider the relationship between representation and the planning/enhancement of the contemporary landscape, in light of the changes and the evolution of GIS techniques.